Technology Enhanced Learning: Students' Views - O'DONNELL, EILEEN; SHARP, MARY (My University, 2011)
User feedback is very important in all areas of computer science especially in the development of computer applications. Hence, student feedback on the use of technology enhanced learning in higher education in Ireland is relevant to the quality of the learning resources to be created by learning designers and academics in the future. The book ?Student Reactions to Learning with Technologies: Perceptions and Outcomes? (Moyle & Wijngaards, 2012) was published by IGI Global in October 2011. This book includes contributions from various authors who are interested in students? feedback regarding how technology has impacted on their educational experience. This book provides feedback from students located in different countries. Chapter 10: ?Students? views of E-Learning: The impact of technologies on learning in higher education in Ireland ? (O'Donnell & Sharp, 2012) provides feedback from three hundred and twenty students to inform learning designers and academics about students? thoughts and opinions on the impact of technologies on learning in higher education in Ireland. This research was conducted in both Trinity College Dublin and the Dublin Institute of Technology. The responses received from the students who kindly participated in this study were analysed and the findings are presented in this chapter. Analysis of the responses received from these students indicates that students are of the opinion that the use of technologies in higher education can beneficially transform learning; however, technologies will never replace lecturers
International Conference on Engaging Pedagogy
International Conference on Engaging Pedagogy (ICEP) 2011
PUBLISHED
National College of Ireland, Dublin
ISBN: 978-1-906878-03-0
Keywords: Technology Enhanced Learning